Control interno para fomentar el desarrollo administrativo, en la caja solidaria Llankaj Warmi de la comunidad de Tagma San José – parroquia San Simón - cantón Guaranda – provincia Bolívar – Periodo 2012 – 2013”. - Agualongo Chela, Klever Germán. (2014)
This research "INTERNAL CONTROL TO PROMOTE THE ADMINISTRATIVE HOUSING DEVELOPMENT PARTNERSHIP LLANKAJ WARMI", aims to provide an instrument of administrative and financial procedures of internal control for the proper management of the resources of the Solidarity Fund. Versa in the bibliographical support related issues, were clarified with the theoretical concepts of internal control in the organization, the same that underlie the development of the internal control system of the Solidarity Fund; starting with its definition, importance, objectives, elements, classification, limitations and organic components of the system of internal control. The methods used in the work of graduation were the inductive, deductive. The types of research were Bibliographic Research Field, Descriptive and Longitudinal, to know the main activity of the organization and its procedures; The Observation, Interview and Survey: and techniques for data collection were also used.